Optimalisasi Kotoran Sapi Menjadi Pupuk Organik untuk Swasembada Pertanian Desa Kelbung Galis Bangkalan - Sama’un Sama’un; Moh Sholeh; Ahmad Bahrudin (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Kelbung Village, Galis sub-district, is geographically located in the eastern part of the City of Bangkalan Regency and is a potential area for the development of agricultural and livestock commodities. The livelihood of the people apart from raising cattle is farming. In addition to topographical conditions, climatic conditions also support this area for the development of various agricultural commodities and beef cattle breeding. This Community Partnership Program (PKM) activity is a team activity from the Bangkalan Ushuluddin Darussalam College of Science with partners, namely livestock farming groups in Kelbung Village, Galis Bangkalan sub-district. One of the problems agreed to be resolved through this program is in the agricultural sector, namely providing counseling and knowledge about making organic fertilizer from waste (cow dung). The target and outcome of the counseling and training activities for making organic fertilizers is that partner groups understand how to make organic fertilizers and apply them to plants. In order to find out the increased understanding of partner farmer groups, an evaluation was designed that was carried out at the beginning (pre-test) and at the end of the activity (post-test). The results of activities in the form of counseling and training can significantly increase the knowledge of partner members regarding the manufacture of organic fertilizers and their use in plants.